Schenker "Time After Time:" A Modified Schenkerian Approach to Improvisations of Recent Jazz Saxophonists. - Destramp, Jessica. (2017)
Abstract: Using music theorist Steve Larson's Schenkerian-oriented work on jazz as a point of departure, I assert that modified Schenkerian techniques can offer new insights about recent jazz saxophone performances. I have transcribed and analyzed Joshua Redman's 2006 performance of "The Surrey with the Fringe on Top," by Rodgers and Hammerstein, from Oklahoma!; Rich Perry's 2007 version of Harry Warren's and Mack Gordon's "There Will Never Be Another You"; and Bob Mintzer's 2007 "Time After Time," written by Sammy Cahn and Jule Styne. The analytic work does not rest on Schenkerian techniques alone; it is supplemented with, for example, the analysis of form and motive, as well as chord-scales (as determined by the features of the individual standards and improvisations) in order to present a more complete picture of how jazz saxophonists are improvising today. The three analyses I present demonstrate connections between the tune and the improvisation- as well as the development of motivic ideas throughout the course of the improvisations- that are perhaps most easily uncovered by Schenkerian tools. These connections and developments are central in creating unified, coherent improvisations with their own narratives- the stated goal for these performers.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Music.; Advisor: Janet Schmalfeldt.; Committee: John McDonald, and Joel Larue Smith.; Keyword: Music.